2021
DOI: 10.21203/rs.3.rs-508711/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accumulation of As and Pb in Vegetables Grown in Agricultural Soils Contaminated by Historical Mining in Zacatecas, Mexico

Abstract: Historical mining activities are a source of environmental pollution that affects the food chain and the health of human beings. The aim of this study was assessment the accumulation of arsenic and lead in vegetables grown in agricultural soils contaminated by old mining in Zacatecas, Mexico. The concentration of arsenic and lead in agricultural soil and edible parts of carrot, garlic, and pepper was analyzed by atomic absorption spectrometry. The soil-vegetable bioconcentration factor and pollution load index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…High Pb concentration in soil suggests an increase in the metal mobility and a higher probability of bioaccumulation. Muñoz et al (2021) identified, in Vetagrande (ZAC), vegetables with Pb concentrations greater than the limits (0.1 mg Pb/kg) established by the Food and Agriculture Organization of the United Nations (FAO); the vegetables analyzed by Muñoz were garlic (Allium sativum, 3.0 mg Pb/kg), carrot (Daucus carota, 5.0 mg Pb/kg), and bell pepper (Capsicum annuum, 9.6 mg Pb/kg) [81]. The health risk was determined by the non-carcinogenic and carcinogenic risks.…”
Section: Contamination Grade In Mining Agricultural and Residential Landmentioning
confidence: 99%
“…High Pb concentration in soil suggests an increase in the metal mobility and a higher probability of bioaccumulation. Muñoz et al (2021) identified, in Vetagrande (ZAC), vegetables with Pb concentrations greater than the limits (0.1 mg Pb/kg) established by the Food and Agriculture Organization of the United Nations (FAO); the vegetables analyzed by Muñoz were garlic (Allium sativum, 3.0 mg Pb/kg), carrot (Daucus carota, 5.0 mg Pb/kg), and bell pepper (Capsicum annuum, 9.6 mg Pb/kg) [81]. The health risk was determined by the non-carcinogenic and carcinogenic risks.…”
Section: Contamination Grade In Mining Agricultural and Residential Landmentioning
confidence: 99%